1981
DOI: 10.1080/03610738108259796
|View full text |Cite
|
Sign up to set email alerts
|

The elderly and informed consent: Effects of vocabulary level and corrected feedback

Abstract: Eighty-seven elderly adults (57-87 years of age) divided into four WAIS vocabulary subgroups (less than 40, 40-49, 50-59, greater than or equal to 60) participated in a study of comprehension and memory of an informed consent procedure. Ss in Group I read the consent form and, with the information sheet still present, answered multiple choice questions covering the main points of information. Feedback and corrected answers were then provided. Ss in Group II read the consent form but did not receive the compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 18 publications
3
44
0
1
Order By: Relevance
“…Nevertheless, certain strategies may help subjects remember the material beyond the initial testing period (Kleinman et al 1996;Taub et al 1981;Tindall et al 1994;Wirshing et al 1998). Interventions that showed a benefit when delayed recall (generally several weeks later) was tested included an additional interaction (telephone call or information visit) with a nurse, (Dodd and Mood 1981;Aaronson et al 1996) informational videotape, (Weston et al 1997) written (vs. or in addition to oral) preoperative information, (Armstrong et al 1997;Askew et al 1990;Morrow et al 1978) simplified and illustrated presentations, (Krynski et al 1994;Tymchuk et al 1988;Tymchuk and Ouslander 1991), and corrected feedback or multiple learning trials (Kleinman et al 1993;Kleinman et al 1996;Taub et al 1981;Wadey and Frank 1997;White et al 1995;Wirshing et al 1998). …”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, certain strategies may help subjects remember the material beyond the initial testing period (Kleinman et al 1996;Taub et al 1981;Tindall et al 1994;Wirshing et al 1998). Interventions that showed a benefit when delayed recall (generally several weeks later) was tested included an additional interaction (telephone call or information visit) with a nurse, (Dodd and Mood 1981;Aaronson et al 1996) informational videotape, (Weston et al 1997) written (vs. or in addition to oral) preoperative information, (Armstrong et al 1997;Askew et al 1990;Morrow et al 1978) simplified and illustrated presentations, (Krynski et al 1994;Tymchuk et al 1988;Tymchuk and Ouslander 1991), and corrected feedback or multiple learning trials (Kleinman et al 1993;Kleinman et al 1996;Taub et al 1981;Wadey and Frank 1997;White et al 1995;Wirshing et al 1998). …”
Section: Study Characteristicsmentioning
confidence: 99%
“…The 11 positive studies included comparisons of simplified with the standard (complex) consent forms (Bjorn et al 1999;Young et al 1990); comparison of uniform total disclosures with individualized disclosures personalized by the physician (Simes et al 1986); a telephone-based intervention to inform patients more thoroughly about a clinical trial (Aaronson et al 1996); a step-wise consent process (Rikkert et al 1997); the use of interviews, repetition, corrected feedback, and multiple learning trials (Carpenter et al 2000;Taub et al 1981;Wirshing et al 1998), and having patients speak or write about the consent information (Sorrell 1991). In two studies, patients served as their own controls, with change over time being the reported outcome measure (Rikkert et al 1997;Wirshing et al 1998).…”
Section: Consent For Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In U.S.-based studies, requiring patients to verbalize risks and benefits themselves 18 or having research staff provide "corrected feedback" to participants has been shown to be effective. 19 Use of simplified material 20 and pictures improved understanding, 21 and another study found patients preferred simplified consent forms. 22 Two studies found that the use of video did not result in improvement of understanding but improved recall one to two months later.…”
Section: Conduct More Empirical Research Testing Interventions To Impmentioning
confidence: 99%